The Gastrointestinal Load of Carbapenem-Resistant Enterobacteriacea Is Associated With the Transition From Colonization to Infection by Klebsiella pneumoniae Isolates Harboring the blaKPC Gene - Migliorini, Letícia Busato; Leaden, Laura; de Sales, Romário Oliveira; Correa, Nathalia Pellegrini; Marins, Maryana Mara; Koga, Paula Célia Mariko; Toniolo, Alexandra do Rosario; de Menezes, Fernando Gatti; Martino, Marines Dalla Valle; Mingorance, Jesús; Severino, Patricia (Frontiers in Cellular and Infection Microbiology, 2022)
Background Healthcare-associated infections by carbapenem-resistant Klebsiella pneumoniae are difficult to control. Virulence and antibiotic resistance genes contribute to infection, but the mechanisms associated with the transition from colonization to infection remain unclear. Objective We investigated the transition from carriage to infection by K. pneumoniae isolates carrying the K. pneumoniae carbapenemase–encoding gene blaKPC (KpKPC). Methods KpKPC isolates detected within a 10-year period in a single tertiary-care hospital were characterized by pulsed-field gel electrophoresis (PFGE), multilocus sequencing typing, capsular lipopolysaccharide and polysaccharide typing, antimicrobial susceptibility profiles, and the presence of virulence genes. The gastrointestinal load of carbapenem-resistant Enterobacteriaceae and of blaKPC-carrying bacteria was estimated by relative quantification in rectal swabs. Results were evaluated as contributors to the progression from carriage to infection. Results No PGFE type; ST-, K-, or O-serotypes; antimicrobial susceptibility profiles; or the presence of virulence markers, such yersiniabactin and colibactin, were associated with carriage or infection, with ST437 and ST11 being the most prevalent clones. Admission to intensive and semi-intensive care units was a risk factor for the development of infections (OR 2.79, 95% CI 1.375 to 5.687, P=0.005), but higher intestinal loads of carbapenem-resistant Enterobacteriaceae or of blaKPC-carrying bacteria were the only factors associated with the transition from colonization to infection in this cohort (OR 8.601, 95% CI 2.44 to 30.352, P<0.001). Conclusion The presence of resistance and virulence mechanisms were not associated with progression from colonization to infection, while intestinal colonization by carbapenem-resistant Enterobacteriacea and, more specifically, the load of gastrointestinal carriage emerged as an important determinant of infection.